Comparative study of the word capacity and episodic memory of patients with degenerative dementia [Estudio comparativo de la capacidad denominativa y la memoria episódica de los pacientes con demencia degenerativa] - Custodio, Nilton (2020)
ABSTRACT Introduction Although the absence of memory impairment was considered among the diagnostic criteria to differentiate Alzheimer's disease (AD) from Behavioural Variant of Frontotemporal Dementia (bvFTD), current and growing evidence indicates that a significant percentage of cases of bvFTD present with episodic memory deficits. In order to compare the performance profile of the naming capacity and episodic memory in patients with AD and bvFTD the present study was designed. Methods Cross-sectional and analytical study with control group (32 people). The study included 42 people with probable AD and 22 with probable bvFTD, all over 60 years old. Uniform Data Set instruments validated in Spanish were used: Multilingual Naming Test (MINT), Craft-21 history and Benson's complex figure, among others. Results: A higher average age was observed among the patients with AD. The naming capacity was much lower in patients with bvFTD compared to patients with AD, measured according to the MINT and the nouns/verbs naming coefficient. All patients with bvFTD, 73.81% of those with AD and only 31.25% of the control group failed to recognise Benson's complex figure. All differences were statistically significant (p < 0.001). Results This study confirms the amnesic profile of patients with AD and reveals the decrease in naming capacity in patients with bvFTD, an area of language that is typically affected early on with executive functions, according to recent findings. Conclusions Patients with AD perform worse in verbal and visual episodic memory tasks, while patients with bvFTD perform worse in naming tasks. These findings open the possibility of exploring the mechanisms of prefrontal participation in episodic memory, typically attributed to the hippocampus.